1989
DOI: 10.1017/s0950268800029952
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of campylobacter from human faeces stored at 4 °C

Abstract: Six hundred and thirteen fresh diarrhoeal faeces were inoculated on Skirrow blood agar (SK), on Preston blood free agar (PBF), and in Campy-thioglycolate broth (CT). After 24 h of storage at 4 degrees C, specimens were again inoculated on SK and PBF, and in Campylobacter enrichment broth (CEB). CT tubes were placed overnight at 4 degrees C. Plates and CEB tubes were incubated at 43 degrees C in microaerophilic conditions. A total of 68 specimens was positive for campylobacter on direct plating. Sixty-four of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…In support of this, Ladron de Guevara et al . [6] previously reported that 16·2% of Campylobacter -positive samples failed to grow when comparing immediate culture with a 24-h delay stored at 4°C; a figure which aligns closely with our finding here. We found that 85·9% of the C. jejuni-/C.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…In support of this, Ladron de Guevara et al . [6] previously reported that 16·2% of Campylobacter -positive samples failed to grow when comparing immediate culture with a 24-h delay stored at 4°C; a figure which aligns closely with our finding here. We found that 85·9% of the C. jejuni-/C.…”
supporting
confidence: 92%
“…Unlike the earlier study [5] in which samples were cultured on the day of receipt, here samples were stored at 4 xC and cultured retrospectively once identified as Campylobacter-positive using the EntericBio method. In support of this, Ladron de Guevara et al [6] previously reported that 16 . 2% of Campylobacter-positive samples failed to grow when comparing immediate culture with a 24-h delay stored at 4 xC ; a figure which aligns closely with our finding here.…”
mentioning
confidence: 67%
“…Although we anticipated differences in the cryoprotective effects of bovine versus human fecal samples, Dan et al (1989), using human fecal samples, reported that at 4°C C. jejuni survived for Ͻ1 month, with or without cryopreservatives. Ladron de Guevara et al (1989) indicated that storage of human feces at 4°C for 24 h significantly reduced numbers of viable C. jejuni. A study by Mills and Gherna (1988) demonstrated that pure cultures of C. jejuni could not maintain viability at Ϫ20°C after storage for 7 months using glycerol as cryopreservative.…”
Section: Resultsmentioning
confidence: 99%